2022
DOI: 10.9744/dimensi.49.1.43-52
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Vertical Greenery on Office Façade Opening to Improve Indoor Light Quality

Abstract: In medium-rise office building on tropical climate, façade fenestration mostly dominated by glass curtain wall. In this case, an effort should be done to control the daylight penetration and to shade glare of low sun angle especially from west orientation. The idea is utilized the vertical greenery system (VGS) on facade opening, how it performs as glare limitation as well as accommodating view. Firstly, the variable of artificial shading to light parameter are studied. Then, the previous research of VGS were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The evaluation of light and thermal aspect as well as the occupant's perception is expected to provide insights to architects and building owners when making decisions for future applications. The effectiveness of perforated metal in regulating lighting is influenced by the size of the hole diameter and spacing, which is closely related to the sun's position [6]. Based on the results, a comparison was carried out between two types of the device with the same openness factor but different dimensions and spacing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of light and thermal aspect as well as the occupant's perception is expected to provide insights to architects and building owners when making decisions for future applications. The effectiveness of perforated metal in regulating lighting is influenced by the size of the hole diameter and spacing, which is closely related to the sun's position [6]. Based on the results, a comparison was carried out between two types of the device with the same openness factor but different dimensions and spacing.…”
Section: Introductionmentioning
confidence: 99%
“…The first sample with a smaller hole and spacing reduced lighting by 39% to 15%, while the second sample with the double dimension had a lower transmission coefficient reduction result of 40% to 32%. [6] Artificial shading devices can be substituted with biotic variants using plant as a natural solar tracker. VGS can be used to prevent radiation naturally and serve as a biotic sun tracker aesthetically [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it was found that vegetation serves as an effective shadow factor that can be compared to various artificial barriers [19,20]. While the thermal parameters, heat transfer, and energy balance of vertical greenery have already been studied and formulated by various investigators [21][22][23] there is still a need to explore the specific mechanism through which plants filter the abundant incoming light on glass facades [24]. This study focuses on leaf area index (LAI) as a quantitative variable to investigate its performance in shading sunlight.…”
Section: Introductionmentioning
confidence: 99%